INFLUENCES OF ANODIZING PARAMETERS OF 2618 AND 7175 ALUMINIUM ALLOYS ON THE THICKNESS OF THE OXIDE LAYER AND ITS RESISTANCE TO PITTING CORROSION - PRAWIRA MINWAL (NIM : 22110035), WAHYUDIN
Aluminum is the material most widely used in commercial aircraft industry. Aluminium as aircraft components widely used in the form of aluminum alloy. Today aluminum alloy developed to obtain material that is light, strong, long service life, low cost production, high tolerance of failure, mechanical properties and good corrosion resistance. Problems are often encountered in the use of aluminum alloy as the material plane that is resistance to corrosion. Therefore, corrosion protection needs to be done on the aluminum alloy. One way that can be used for corrosion protection of Chromic Acid Anodize (CAA). A series of experiments were carried out at various conditions to study the effects of variations in temperature, time and voltage on the thickness of the anodizing coating with Analysis of Variance (ANOVA) method and studied the effect of variations, temperature, time, voltage and sealing solutions to the corrosion resistance of coatings in salt spray test. Voltage applied to the material 2618 is 35-45 volts, while for 7175 the material is 15-25 volts. Chromic acid solution using only one concentration. Anodizing temperature varied at 25ºC, 30ºC and 40ºC, while the anodizing time was varied for 20 minutes, 40 minutes and 60 minutes. After the anodizing process, the process of sealing was done by using two types of solutions namely Na2Cr2O7 and K2Cr2O7. The experimental results show the highest oxide layer thickness for aluminum alloy 2618 reached the anodizing process with voltage of 35 V and a temperature of 40oC for 60 minutes, whereas the 7175 alloy layer thickness is achieved at the highest voltage of 15 V and a temperature of 25oC for 60 minutes. Increasing temperature and time of anodizing will increase the thickness of the layer while the effect of increasing the voltage will depend on the conductivity and resistance of the alloy type. Resistance to corrosion of the alloy 2618 showed that there are 25% of samples that are not corroded where 13% of samples on-sealing with a solution Na2Cr2O7 and 11% of samples on-sealing with a solution of K2Cr2O7. In 7175 aluminum alloy, there are 30% of samples did not experience corrosion pitting which 13% of samples in-sealing with a solution Na2Cr2O7 and 16% of samples in-sealing with a solution of K2Cr2O7. High layer thickness can not preclude the occurrence of pitting corrosion due to the oxide layer on the alloy surface is uneven. At the time, the use of dichromate sealing is not able to withstand attacks because the Cl- ion reaction is the transformation of the ion chromate ion dichromate.